2000
DOI: 10.1007/s007840000079
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of resorbable and nonresorbable guided tissue regeneration membranes in cultures of primary human periodontal ligament fibroblasts and human osteoblast-like cells

Abstract: The purpose of this study was (a) to evaluate the cytocompatibility of three resorbable and nonresorbable membranes in fibroblast and osteoblast-like cell cultures and (b) to observe the growth of those cells on the various barriers by scanning electron microscopy (SEM). Primary human periodontal ligament fibroblasts (HPLF) and human osteoblast-like cells (SAOS-2) were incubated with nonresorbable polytetrafluoroethylene (ePTFE) barriers and resorbable polylactic acid as well as collagen membranes. Cytotoxic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 20 publications
2
53
0
4
Order By: Relevance
“…Since the experiments conducted in the present study were in vitro ones of relatively short duration, the resorption of the various membranes did not most likely factor into the results with respect to the enhancing effects of the nCS. However, our data are consistent with those of others that suggest that collagen membranes can support the growth/proliferation of these cells [20,21]. It is interesting to note that the nCS coating did not significantly increase this parameter as measured with the MTT assay for the BioGide® membrane and had only relatively small effects for the RCM6 TM and HeliPLUG® products.…”
Section: Discussionsupporting
confidence: 81%
“…Since the experiments conducted in the present study were in vitro ones of relatively short duration, the resorption of the various membranes did not most likely factor into the results with respect to the enhancing effects of the nCS. However, our data are consistent with those of others that suggest that collagen membranes can support the growth/proliferation of these cells [20,21]. It is interesting to note that the nCS coating did not significantly increase this parameter as measured with the MTT assay for the BioGide® membrane and had only relatively small effects for the RCM6 TM and HeliPLUG® products.…”
Section: Discussionsupporting
confidence: 81%
“…However, the e-PTFE and polylactic acid membranes induced slight to moderate cytotoxic reactions that may reduce cellular adhesion. 36 One of our preceding studies used an immunohistochemical method to localize postulated adhesion molecules (␣2, ␣3, and ␣6␤1) at the interface of PDCM and adjacent connective tissue. The results suggest that PDCM possesses a good-quality high protein bonding surface to achieve tissue integration with adjacent connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, it has also been shown that not all cell types show the same affi nity for a given surface. 28 The aim of the GTR procedure is the regeneration of a fully functional periodontium, including new cementum and periodontal ligament (PDL), as well as new bone.…”
Section: Cells Used For In Vitro Studiesmentioning
confidence: 99%